Unlocking Reversible Mn2+/MnO2 Chemistry in Semisolid Slurry Electrodes for High-Performance Aqueous Zn–Mn Batteries - Yang, Zefang; Zhang, Qi; Hu, Chao; Tang, Yougen; Li, Jinchi; Wang, Qi; Zhou, Wanhai; Chao, Dongliang; Wang, Haiyan (Nano-Micro Letters, 2026)
Electrolytic Zn–MnO2 batteries are promising candidates for safe and sustainable energy storage owing to their high voltage, environmental benignity, and cost-effectiveness. However, practical applications are hindered by the poor conductivity and the irreversible dissolution of conventional ε-MnO2 deposits. Herein, we report a scalable semisolid slurry electrode architecture that enables stable MnO2 deposition/dissolution using a three-dimensional percolating network of carbon nanotubes (CNTs) as both conductive matrix and deposition host. The slurry system promotes the formation of highly conductive γ-MnO2 owing to enhanced charge transfer kinetics, enabling overall dissolution rather than the localized separation typically seen in traditional electrodes. The Zn–MnO2 slurry cell exhibits a reversible areal capacity approaching 60 mAh cm−2. Moreover, the flowable nature of the slurry allows electrochemically inactive MnO2 formed during dissolution to be reconnected and reactivated by CNTs in the rheological network, ensuring deep utilization and cycling stability. This work establishes a slurry electrode strategy to improve electrolytic MnO2 reactions and offers a viable pathway toward renewable aqueous batteries for grid-scale applications. Highlights: 1 A semisolid MnO2 slurry electrode enables reversible MnO2 deposition/dissolution within a CNT-percolated conductive network, achieving a high areal capacity of 60 mAh cm−2 2 The slurry system promotes the formation of highly conductive γ-MnO2 and achieves uniform MnO2 dissolution through enhanced charge transfer. 3 The MnO2 slurry electrode offers strong scalability and regenerability, retaining 100% capacity after 180 cycles and reactivating inactive MnO2 via percolation.